TSUNAMI, MIGRASI TERPAKSA, DAN RENCANA PENGUNGSI DI ACEH BARAT DAN NAGAN RAYA - Abdur Rofi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2005)
Research of the forced migration and Internal Displaced Persons (IDPs) intentions after the tsunami disaster in Aceh Barat andNagan Raya districts of NAD is focusing on some questions regarding the migration patterns and IDP households plans related to their home stay and occupation plans in next three months. This research used cluster sample survey with probability proportional to size (PPS) and the figures and locations for IDPs whith provided by the TNI (Indonesian National Army) as January of23,2005 as a sample frame. Research found that IDPs tend to stay in the near area to their original place.